Extracellular Vesicles in Mycobacteria and Tuberculosis - Mehaffy, Carolina; Ryan, Joan M.; Kruh-Garcia, Nicole A.; Dobos, Karen M. (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculosis (TB) remains a public health issue causing millions of infections every year. Of these, about 15% ultimately result in death. Efforts to control TB include development of new and more effective vaccines, novel and more effective drug treatments, and new diagnostics that test for both latent TB Infection and TB disease. All of these areas of research benefit from a good understanding of the physiology of Mycobacterium tuberculosis (Mtb), the primary causative agent of TB. Mtb secreted protein antigens have been the focus of vaccine and diagnosis research for the past century. Recently, the discovery of extracellular vesicles (EVs) as an important source of secreted antigens in Mtb has gained attention. Similarly, the discovery that host EVs can carry Mtb products during in vitro and in vivo infection has spiked interest because of its potential use in blood-based diagnostics. Despite advances in understanding the content of Mtb and Mtb-infected host extracellular vesicles, our understanding on the biogenesis and role of Mtb and host extracellular vesicles during Mtb infection is still nascent. Here, we explore the current literature on extracellular vesicles regarding Mtb, discuss the host and Mtb extracellular vesicles as distinct entities, and discuss current gaps in the field.